New focus on regulation of the rod photoreceptor phosphodiesterase. (August 2021) - Gulati, Sahil; Palczewski, Krzysztof
Abstract: Rod photoreceptor phosphodiesterase (PDE6) is the key catalytic enzyme of visual phototransduction. PDE6 is the only member of the phosphodiesterase family that consists of a heterodimeric catalytic core composed of PDE6α and PDE6β subunits and two inhibitory PDE6γ subunits. Both PDE6α and PDE6β contain two regulatory GAF domains and one catalytic domain. GAF domains and the tightly bound PDE6γ subunits allosterically regulate the activity of the catalytic domain in association with the GTP-bound transducin alpha subunit (Gtα-GTP ). Recent cryo-electron microscopy structures of the PDE6αγβγ and PDE6αγβγ-(Gtα-GTP )2 complexes have provided valuable knowledge shedding additional light on the allosteric activation of PDE6 by Gtα-GTP . Here we discuss recent developments in our understanding of the mechanism of PDE6 activation. Highlights: The PDE6αγβγ-(Gtα-GTP )2 structure shows a crosstalk between Gtα-GTP and the catalytic domain of the adjacent PDE6 subunit. The Pt-motif has a structural role in PDE6 complex formation. T he comparison of PDE6αγβγ with PDE6αγβγ-(Gtα-GTP )2 complex suggest a possible membrane-anchoring role of the Pt-motif.